Pengaruh Profitabilitas, Likuiditas, Kepemilikan Manajerial, dan Kebijakan Dividen Pada Nilai Perusahaan - Syahla , Elytha; Mochtar, Raja Ade Fitrasari (Akuntansi & Ekonomika, 2024)
The research examines and analyzes the impact of profitability, liquidity, managerial ownership, and dividend policy on firm value in companies operating in the infrastructure, transportation, and logistics sectors listed on IDX from 2020 to 2022. The study population includes 169 companies. The data sampling used a purposive sampling technique, resulting in 20 companies, with multiple linear regression as the data analysis tool. Profitability and liquidity individually have a positive effect on firm value. Managerial ownership and dividend policy do not affect firm value. Overall, profitability, liquidity, managerial ownership, and dividend policy collectively influence firm value.